Kepatuhan Mengonsumsi Obat Pasien Hipertensi Di Denpasar Ditinjau Dari Kepribadian Tipe A Dan Tipe B - Evadewi, Putu Kenny Rani; Suarya, Luh Made Karisma Sukmayanti (Jurnal Psikologi Udayana, 2013)
The changes of life style in today’ such as reductions in physical activity led to the emergence of a variety of chronic diseases such for instance hypertension. Hypertensive patients are required to take medication on a regular basis, so that the necessary compliance in taking the drug. There are various factors that affect adherence taking the drug, one of which is personality. Personality type A and type B is said to have a close relationship with chronic disease. This study aims to determine the compliance of hypertensive patients taking the drug in Denpasar in terms of personality type A and type B.   This research is quantitative comparative method. Sampling technique used is purposive random sampling. The population in this study were hypertensive patients in Denpasar with the number of respondents 267 subjects. Number of samples with type A personalities are 135 subjects and type B personality as much as 132 subjects. Data analysis methods used are independent samples t test (p<0,05).   The results indicate there are differences in medication adherence among hypertensive patients taking personality types A and B (significance p=0.001). More respondents overall had a bad drug taking compliance (189 subjects) compared to subjects who had good adherence (78 subjects). Moreover, taking medication compliance analysis based on age, sex, duration of hypertension showed more male subjects, ages 52 to 59 years, with hypertension 6 to 10 years which may had a role in adherence patients taking medication.   Keywords: Compliance of medication consumption, type A and type B personalities, hypertension